Equivalent damage-healing approach to residual fatigue life prediction for copper film by laser repair. (July 2015) - Liu, Xiao-Dong; Shang, De-Guang; Zhang, Li-Hong; Guo, Yu-Bo; Sun, Yu-Juan; Chen, Tao; Guo, YB; Barkey, ME
A healing method for fatigue damage was investigated by laser shock peening and laser irradiation with excimer laser for polycrystalline copper film. It is found that the sum of the consumed fatigue ductility and the total fatigue ductility for the damaged specimen after both laser treatments is equal to the total fatigue ductility for the undamaged specimen after both laser treatments. The evolution of the damage healing can be replaced by that for the undamaged specimen after laser treatment. Based on the equivalent fatigue damage evolution, a residual fatigue life prediction method is proposed during the damage-healing process for the copper specimen. The predicted lives by the proposed method agree well with the experimental results.